Blake’s Allegory of Tolerance - Fogarasi, György (FOCUS: Papers in English Literary and Cultural Studies, 2020)
Glimpsing at the critical discourse of recent decades, one may have the impression that something has become increasingly intolerable about tolerance. The growing number of books on the subject, including surveys of the cultural diversity of related notions, seems to suggest that a growing number of doubts surround not only the feasibility of global practices or institutions of toleration but the status of the very concept of tolerance as well. Arguments about the paradox of tolerance, its boundaries, its difficulty, its crisis, or even its dangers, to mention but a few of the multitude of concerns, are often coupled with eff orts to delineate, and thereby to limit, its scope through distinctions between, say, tolerance and forbearance, toleration and tolerance, acceptance and tolerance, recognition and tolerance, hospitality and tolerance, and so forth. As a proponent of the latter divide, Jacques Derrida has argued that, unlike hospitality, the concept of tolerance still seems to imply a notion of power and sovereignty which should be critically superseded and replaced by a disposition that is no longer an “invitation” of the other but an openness to its unexpected and incalculable “visitation” (Derrida, “Autoimmunity” 129). For Derrida, tolerance could still be described as a conditional mode of hospitality, whereas what we would really need is an absolute opening toward alterity or futurity, one which leaves behind any attempt at calculating what is to come, and is in that sense purely unconditional. Such an openness could rightfully be called hospitality per se.